Evaluation of the performance of magnetic zeolite nanocomposites in removing various water contaminants as heavy metals, organic pollutants, and emerging contaminants: A review - Koffi Sossou; S. Bala Prasad; Eyram Komlavi Agbotsou; Halarou Saidou Souley (Next Nanotechnology, 2024)
The presence of organic and inorganic contaminants such as pesticides, antibiotics, dyes, and heavy metals poses a risk to a human and the environment and therefore needs to be removed. The combination of natural zeolites and magnetic nanoparticles is employed as an excellent adsorbent for these pollutants removal from water. Magnetic zeolites are synthesized by incorporating magnetic nanoparticles, such as iron oxides or ferrites, into the zeolite framework. Various techniques, including co-precipitation, impregnation, and hydrothermal synthesis, have been employed by researchers to create the necessary magnetic zeolite composites and employed them for removing or reducing recalcitrant pollutants present in water or aqueous solutions. Magnetic zeolites have shown great promise in the removal of contaminants present in water. One of its best sides is its ability to separate and reuse materials easily. This review emphasizes magnetic zeolite as an effective adsorbent for water remediation and demonstrates its potential for water treatment. Magnetic zeolite can be used especially in regions where water treatment technologies are not yet met and can address waterborne disease issues. Due to its magnetic properties, and easier recovery and reuse of the adsorbents, the magnetic zeolite adsorption method is cost-effective and convenient